Sustainable nutrient management: Exploring fulvic acid, chelated zinc application methods and rates for improved Maize growth and productivity - Rohit, T; Anita, J; Sarang, H S (Plant Science Today, 2025)
The performance of maize is frequently limited by scarcity of micronutrients, especially zinc, which is essential for numerous physiological functions. The present study investigates the impact of different application methods and doses of fulvic acid (FA) and chelated zinc (Zn-EDTA) on the growth and productivity of maize (Zea mays L.), in response to the increasing global demand for this vital crop. This study was performed at the student farm of Lovely Professional University during the Kharif season of 2023-2024, utilizing a randomized block design with nine treatments, which included soil and foliar sprays of fulvic acid, and Zn-EDTA at different concentrations. Essential growth parameters such as plant height, stem girth, number of leaves, leaf area, chlorophyll index, fresh and dry weight, yield attributes and yield were recorded at various growth stages. The treatment of soil fulvic acid and foliar Zn-EDTA at 2.5 kg ha-1 resulted in maximum plant height (152.3 cm), stem girth (2.10cm), leaf area (494.06 cm2 ), chlorophyll index (48.36 SPAD), fresh and dry weight (191.5g, 86.2g), number of cobs per plant (2), rows per cob (16), grains per cob (48.33), length of cob (16.96 cm) and weight of cob (150.4 g). At the same time, the minimum values have been recorded with the sole application of 100% RDF. This study emphasizes the synergistic advantages of combining bio stimulants and micronutrients to improve maize growth and yield, providing significant insights for formulating sustainable agricultural methods that promote crop productivity and nutrient utilization efficiency.